Mismatch: a comparative study of vitamin D status in British-Bangladeshi migrants. Issue 1 (25th January 2021) - Smith, Nicholas; Sievert, Lynnette Leidy; Muttukrishna, Shanthi; Begum, Khurshida; Murphy, Lorna; Sharmeen, Taniya; Gunu, Richard; Chowdhury, Osul; Bentley, Gillian R
Abstract: Background and objectives: Low levels of vitamin D among dark-skinned migrants to northern latitudes and increased risks for associated pathologies illustrate an evolutionary mismatch between an environment of high ultraviolet (UV) radiation to which such migrants are adapted and the low UV environment to which they migrate. Recently, low levels of vitamin D have also been associated with higher risks for contracting COVID-19. South Asians in the UK have higher risk for low vitamin D levels. In this study, we assessed vitamin D status of British-Bangladeshi migrants compared with white British residents and Bangladeshis still living in Bangladesh ('sedentees'). Methodology: The cross-sectional study compared serum vitamin D levels among 149 women aged 35–59, comprising British-Bangladeshi migrants ( n = 50), white British neighbors ( n = 54) and Bangladeshi sedentees ( n = 45). Analyses comprised multivariate models to assess serum levels of 25-hydroxyvitamin D (25(OH)D), and associations with anthropometric, lifestyle, health and migration factors. Results: Vitamin D levels in Bangladeshi migrants were very low: mean 25(OH)D = 32.2 nmol/L ± 13.0, with 29% of migrants classified as deficient (<25 nmol/L) and 94% deficient or insufficient (≤50 nmol/L). Mean levels of vitamin D were significantly lower among British-Bangladeshis compared with Bangladeshi sedentees (50.9 nmol/L ± 13.3, P < 0.001) and were also lower than in white British women (55.3 nmol/L ± 20.9). Lower levels of vitamin D were associated with increased body mass index and low iron status. Conclusions and implications: We conclude that lower exposure to sunlight in the UK reduces vitamin D levels in Bangladeshi migrants. Recommending supplements could prevent potentially adverse health outcomes associated with vitamin D deficiency. Lay Summary: Vitamin D deficiency is one example of mismatch between an evolved trait and novel environments. Here we compare vitamin D status of dark-skinned British-Bangladeshi migrants in the UK to Bangladeshis in Bangladesh and white British individuals. Migrants had lower levels of vitamin D and are at risk for associated pathologies.